Rational design and generation of recombinant control reagents for bispecific antibodies through CDR mutagenesis - Choi, Bryan D. (2013)
Developments in the field of bispecific antibodies have progressed rapidly in recent years, particularly in their potential role for the treatment of malignant disease. However, manufacturing stable molecules has proven to be costly and time-consuming, which in turn has hampered certain aspects of preclinical evaluation including the unavailability of appropriate “negative” controls. Bispecific molecules (e.g., bispecific tandem scFv) exhibit two specificities, often against a tumor antigen as well as an immune-activation ligand such as CD3. While for IgG antibodies, isotype-matched controls are well accepted, when considering smaller antibody fragments it is not possible to adequately control for their biological activity through the use of archetypal isotypes, which differ dramatically in affinity, size, structure, and design. Here, we demonstrate a method for the rapid production of negative control tandem scFvs through complementarity determining region (CDR) mutagenesis, using a recently described bispecific T-cell engager (BiTE) targeting a tumor-specific mutation of the epidermal growth factor receptor (EGFRvIII) as an example. Four independent control constructs were developed by this method through alteration of residues spanning individual CDR domains. Importantly, while target antigen affinity was completely impaired, CD3 binding affinity was conserved in each molecule. These results have a potential to enhance the sophistication by which bispecific antibodies can be evaluated in the preclinical setting and may have broader applications for an array of alternative antibody-derived therapeutic platforms.